Bioactive flavonoid glycosides from Whole Plants of Iris japonica. (March 2017) - Shi, Guo-Ru; Wang, Xin; Liu, Yan-Fei; Zhang, Chun-Lei; Ni, Gang; Chen, Ruo-Yun; Yu, De-Quan
Graphical abstract: Highlights: Three new flavonoid glycosides (1–3 ) and eight known anlogues were reported. Hepatoprotective activities and Aldose reductase activity of compounds1 –11 were evaluated. Compounds2, 10 and11 (10 μM) showed a certain degree inhibitory activities against aldose reductase. Compounds1, 4 and9 (10 μM) exhibited pronounced hepatoprotective activities against APAP-induced HepG2 cell damage in vitro. Abstract: Phytochemical investigation of the ethanol extract of whole plants of Iris japonica led to the isolation of three new and eight known analogues of flavonoid glycosides. The newly isolated structures were determined by spectroscopic and chemical methods as tectorigenin-7- O -β-d -glucopyranosyl (1 → 3)- O -β-d -glucopyranoside (1 ), tectorigenin-7- O -β-d -deoxyallopyranoside (2 ), and tectorigenin-7- O -β-d -quinovopyranoside (3 ). In addition, all of the compounds were tested for their hepatoprotective activities against APAP-induced HepG2 cell damage and inhibitory activities against aldose reductase. Compounds2, 10 and11 (10 μM) showed a certain degree of inhibitory activity against aldose reductase, and compounds1, 4 and9 (10 μM) exhibited pronounced hepatoprotective activities against APAP-induced HepG2 cell damage in vitro.